2019
DOI: 10.1016/j.actamat.2019.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication and characterization of FeAl-based metallic-intermetallic laminate (MIL) composites

Abstract: FeAl-based MIL composites of various iron alloys were fabricated with an innovative "multiple-thin-foil" configuration and "two-stage reaction" strategy. Alternating stacked metal foils were reactive sintered via SPS at 600 o C and 1000 o C to grow intermetallics. The "multiple-thin-foil" configuration reduces reaction time, enables local chemical composition control and allows metal/intermetallic combinations, which cannot be produced via the conventional methods. Fe-FeAl, 430SS-FeAl, and 304SS-FeAl MIL compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Nanolayered, two-phase FeAl/FeAl 2 composites have been studied at elevated temperatures, but in this case, the FeAl 2 phase creeps (31). To form a nanolayered Fe-Al system with an even higher density of biphase interfaces, stacks of multiple Fe/FeAl alloy foils were sintered (32). While high, room-temperature strength was achieved, the Fe/FeAl interfaces between the foils eventually delaminated under further deformation (32).…”
Section: Introductionmentioning
confidence: 99%
“…Nanolayered, two-phase FeAl/FeAl 2 composites have been studied at elevated temperatures, but in this case, the FeAl 2 phase creeps (31). To form a nanolayered Fe-Al system with an even higher density of biphase interfaces, stacks of multiple Fe/FeAl alloy foils were sintered (32). While high, room-temperature strength was achieved, the Fe/FeAl interfaces between the foils eventually delaminated under further deformation (32).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, a CNN trained on a small subset of patterns belonging to each phase produces the phase map seen in Figure 4f. While the phases are not as perfectly linear as in Figure 4e, it is likely that the merging of phases at their borders is real to some degree according to the analysis performed by Wang et al (2019) and their observation that crystal orientation influences the diffusion rates. Otherwise, the phase map is in good agreement with the expected results, and the CNN-based EBSD method is adept at separating diffraction patterns based on space groups and small changes in chemistry within the same space group.…”
Section: Resultsmentioning
confidence: 95%
“…Six different multiphase materials were selected for demonstrating the proposed phase-mapping methodology: (1) a rutilated quartz sample, (2) a sample of the Campo del Cielo meteorite, from the Chaco Province, Argentina, (3) an arc-melted ingot of Ni 80.8 B 13.6 Si 5.4 Fe 0.2 (at%) blended with 40 wt% eutectic tungsten carbide (a metal matrix composite) (Maroli & Liu, 2017), (4) an Fe–Al metallic–intermetallic laminate (MIL) composite (Wang et al, 2019), (5) a thermally cycled MCrAlY-based thermal barrier coating (Evans et al, 2001; Mercer et al, 2006; Pollock et al, 2012), and (6) a sample of 430 stainless steel. Diffraction patterns from 28 other materials, detailed in Kaufmann et al (2020), were utilized for training the CNN-based model for Bravais lattices demonstrated herein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CBED is limited by intense sample preparation, small areas of analysis, and substantial operator experience (Vecchio & Williams, 1987, 1988; Williams et al, 1991). In comparison, EBSD can be performed on large samples (Bernard et al, 2019; Hufford et al, 2019; Wang et al, 2019; Zhu et al, 2020), including three-dimensional EBSD (Calcagnotto et al, 2010), with high precision (~2°), high misorientation resolution (0.2°) and high spatial resolution (~40 nm) (Chen et al, 2011). Furthermore, the diffraction patterns collected in EBSD contain many of the same features observed in CBED, including excess and deficiency lines and higher-order Laue zone (HOLZ) rings (Michael & Eades, 2000; Winkelmann, 2008).…”
Section: Introductionmentioning
confidence: 99%